PHYTOCHEMICAL INVESTIGATION AND PHARMACOLOGICAL EVALUATION OF ERYTHRAEARAMOSISSIMA - G. Rahman; R. A. Khan (Journal of Animal and Plant Sciences, 2017)
Erythraea ramosissimais traditionally used for the treatment of various human diseases. In the present study was aimed at the in-vitro pharmacological and phytochemical analysis of the methanol extract of Erythraea ramosissima. The sample extract of Erythraea ramosissima showed potent antioxidant activities (98.1±5.2%) inhibition of DPPH, Hydrogen peroxide scavenging activity was (95.1±8.4%), total antioxidant activity was 92.1±5.4 and ABTS scavenging activity of the extract was 94.1±5.4 at 3000µg/ml.Qualitative analysis reveals the presence of saponins, tannins, anthraquinons, alkaloids, coumarins and flavonoids.I the cytotoxicity assay, at 3000μg/mlconcentrations maximum death of brine shrimp was reported. In the light of the present result it is inferred that methanolic extract of Erythraea ramosissima can be used as a free radicle scavenger and as an anticancer agent.
Keywords: Erythraea ramosissima; scavenging activity DPPH; ABTS; phenolics; flavonoid compounds; cytotoxicity